Exploring the relationship between sense of ownership and employee behavior in an organization: A study on siemens pakistan - Rizvi, Syed Qamber Abbas (2010)
In order to get success in competitive business environment, organizations emphasize on maintaining productive and motivated workforce within their offices and Sense of Ownership has been considered as key tool to achieve this. The term “sense of ownership” is frequently cited as a significant characteristic of employee behavior. While there is increasing use of the terms ownership or sense of ownership, there is a paucity of research regarding what these terms mean, how this body of knowledge influences employee behavior, and the various approaches that can be applied in contemporary research and practice. A sense of ownership in an organization described as a concept through which employee feel like an owner while performing their jobs and have influence over decisions, and take responsibility for the outcome. Applying the concept of ownership can increase the productivity and also help to develop motivated environment in the organization. Sense of ownership incorporates personalization, sense of control, territoriality, and involvement. In addition, the potential for ownership can be understood in part by examining the capacity for and quality of trust. Implications are discussed regarding how this sense of ownership advances in modern day organizational environment and how relevant employees consider it for their behavior in the organization and what sort of implementations organization should do to nurture this feeling .